การประเมินสภาพการขาดน้ำของไม้ประดับบางชนิดสำหรับสวนหลังคา - หนูสวัสดิ์ กนกรัตน์; พิชกรรม ณัฏฐ; บุญกอแก้ว พัชรียา; พิชกรรม อุษณีษ์ (Thai Journal of Science and Technology, 2019)
Abstract “Green roof” is a considerable solution to increase urban green area. Plants cultivated on the rooftop inescapably encountering drought and severe heat conditions. This study aimed to evaluate the water-deficit tolerant ability of some ornamental plants for roof garden utility. Non-irrigated rooftop model was constructed in a greenhouse at Mahidol University, Nakhon Pathom province. Fifteen ornamental plants were observed under two conditions, i.e. watering and non-watering, for seven days. Water-deficit tolerant ability was evaluated by beauty scoring. Liriope muscari (Decne.) L.H. Bailey, Cyanotis obtusa (Trimen) Trimen and Allium schoenoprasum L. showed the high tolerance ability to water-deficit by seven days leading to be suitable plants for roof garden by watering once a week. Moreover, Pilea libanensis Urb. and Plectranthus scutellarioides (L.) R.Br. also had high tolerance by five days. The short period plants for three days were Eleocharis sp., Fimbristylis ovata (Burm.f.) J.Kern, Zephyranthes candida (Lindl.) Herb. and Pennisetum setaceum (Forssk.) Chiov., whereas Leucanthemum vulgare (Vaill.) Lam., Rhynchospora nervosa (Vahl.) Boeckeler, Acalypha wilkesiana MÜll.Arg., Trachelospermum jasminoides (Lindl.) Lem., Coreopsis rosea Nutt. and Achillea millefolium L. showed the lowest tolerant ability to water-deficit by one day and might not be utilized for green roof cultivation. Keywords: drought tolerance plant; green roof; landscape